KEMAMPUAN MENYIMAK BERITA MENGGUNAKAN MEDIA AUDIO VISUAL SISWA KELAS VIII SMPN1 PANCUNG SOAL KABUPATEN PESISIR SELATAN TAHUN PELAJARAN 2012/2013 - Putra, Ilwandi; Eska, Wirnita; Nisja, Indriani (Pendidikan Bahasa Indonesia, 2013)
This research is motivated by three reasons, first, the students listened to lack of concentration in the material submitted by teachers. Second, studentsâ listening ability has not been optimal. Third, the lack of media in teaching listening. This study aimed to determine the ability of listening to the news using audio-visual media eighth grade students of SMP Negeri 1 Pancung Soal Kabupaten Pesisir Selatan. This research is quantitative research using descriptive methods. The population in this study is the eighth grade students of SMP Negeri 1 Pancung Soal Kabupaten Pesisir Selatan, amountingÂ to132 people. Samples taken in this study amounted to 34 people. Samping technique proportionate stratified random sampling. The instrument used is a matter of objective test sheets given to students with four alternative answers.Based on the data analysis of the research that has been done that, the ability to listen to news eighth grade students of SMP Negeri 1 Pancung Soal Kabupaten Pesisir Selatan problem with news items why the highest score by an average of 85% which is in good qualification. The ability to listen to what news items (anything) with an average value of 80% which is in qualification. The ability to listen to the news element how with an average value of 81 % which is in good qualification. The ability to listen to the news element who with an average value of 81 % which is in good qualification. The ability to listen to studentsâ news items where with an average value of 79 % which is in good qualification. This ability to listen to students when the news element with an average value of 78 % which is in good qualification. In general it can be concluded students of SMP Negeri 1 Pancung Soal Kabupaten Pesisir Selatan motivated to listen to the news using audio-visual media. The ability to listen to news student of SMP Negeri 1 Pancung Soal Kabupaten Pesisir Selatan in general are seen in both qualifying with an average value of 79 % above the minimum completeness criteria (KKM).